Isolasi Bakteri Selulolitik dari Buah Kopi Robusta (Coffea canephora) dan Uji Kemampuan Degradasi pada Buah Kopi - Rosalia, Merlyna; Adiartayasa, Wayan; Wirawan, I Gede Putu (Nandur; Vol 1 No 1 (2021), 2021)
Coffee fruit contains high cellulose and lignin. Cellulose is the most abundant polysaccharide found in plants, cellulose in nature forms crystals so that cellulose is difficult to degrade. Cellulose can be broken down using cellulase enzymes produced by microorganisms. One of the microorganisms capable of producing cellulase enzymes which are used to hydrolyze cellulose into simpler products, namely glucose, is cellulolytic bacteria. The purpose of this study was to identify bacterial isolates that ferment in coffee cherries. The isolation results obtained 97 bacterial colonies that grew, based on observations of color, shape, edges, and surface, they could be grouped into four groups of bacterial isolates named M1, M2, M3, and M4 bacterial isolates, with each cellulolytic index (IS) of 3,00; 0,75; 2,00 and 3,00. The results of the gram stain test obtained one gram-negative bacterial isolate (M2 rod-shaped) and three gram-positive bacterial isolates (M1 in the form of a focus, M3 and M4 in the form of a rod). Bacterial isolates M1 and M3 degraded the earliest coffee cherries with an average of 2.66 days after inoculation and no later than 6 day after inoculation in M2M4 and M3M4 bacterial isolates. The ability to degrade bacterial isolates in coffee cherries was obtained 2 - 5.34 days faster than the control.